Evaluation of Unsteady Non-Harmonic Fields in Microwave Devices. II. Decomposition in the Partial Oscillators - Gritsunov, A. V. (My University, 2005)
Decomposition of electrodynamic system field in a set of coupled partial oscillators (oscillets) is described. This is a "large-scale" alternative to the FDTD and FETD methods, as the oscillet "lattice" spacing is determined by physical reasons (upper bound of considered wavenumbers) rather than computational ones. The lattice approximation is adaptable to anisotropic media, because the model of coupled partial oscillators is close to the physical mechanism causing this phenomenon (i.e., the atomic oscillations). The fields in a nonlinear or non-stationary medium also can be expanded in a set of nonlinearly coupled nonlinear or parametric oscillators.
Keywords: electrodynamic system; partial mode; Fourier series